EVALUASI EFEKTIVITAS PROGRAM PERCEPATAN PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI BADAN PERTANAHAN NASIONAL KOTA TANGERANG SELATAN TAHUN 2017-2020 - Farras Fakhirah T; Sinta Ningrum; Nina Karlina (Universitas Padjadjaran, 2022)
The background of this research is phenomenon of the large number of land parcels in Indonesia that haven’t been registered and have land certificates as legal evidence. The implication is the rise of cases of land disputes and conflicts in Indonesia. Pendaftaran Tanah Sistematis Lengkap Program (PTSL) was launched as a solution to address these problems. This program is implemented throughout Indonesia, including the National Land Agency of South Tangerang City. The PTSL program in South Tangerang City was implemented in 2017-2020. During its implementation, it was found that the target field was not achieved and the certificate completion was slow, so the authors were interested in researching more deeply.The purpose of this research was to find out how to evaluate by looking at the performance of the PTSL program at the National Land Agency of South Tangerang City in 2017-2020. The research approach used is a quantitative approach. Data collection techniques through documentation studies, literature studies, and interviews. The data analysis technique used is value for money analysis and cost effectiveness analysis The results showed that the PTSL Program at the South Tangerang City Land Agency is ineffective. This can happen because the achievement of output only reached 90.63%. There were obstacles in the 2019 fiscal year related to the difficulty of the community in completing the required documents and the lack of human resources.The, the results of the calculation of cost effectiveness analysis show that the PTSL program is a program with a low cost that is feasible to run when compared to the issuance of land certificates through the routine program. Penelitian ini dilatarbelakangi dari suatu fenomena banyaknya bidang tanah di Indonesia yang belum terdaftar dan memiliki sertifikat tanah sebagai bukti yang sah secara hukum. Implikasi nya yaitu maraknya kasus sengketa dan konflik pertanahan di Indonesia. Program Pendaftaran Tanah Sistematis Lengkap (PTSL) diluncurkan sebagai solusi untuk menjawab permasalahan tersebut. Program ini dilaksanakan diseluruh wilayah Indonesia, termasuk Badan Pertanahan Nasional Kota Tangerang Selatan. Program PTSL di Kota Tangerang Selatan dilaksanakan pada tahun 2017-2020. Selama pelaksanaannya, ditemukan bahwa target bidang tidak tercapai dan penyelesaian sertifikat yang lambat, sehingga penulis tertarik untuk meneliti lebih dalam.Tujuan dari penelitian ini untuk mengetahui kinerja program Pendaftaran Tanah Sistematis Lengkap (PTSL) di Badan Pertanahan Nasional Kota Tangerang Selatan tahun 2017-2020. Pendekatan penelitian yang digunakan adalah pendekatan kuantitatif. Teknik pengumpulan data melalui studi kepustakaan dan wawancara. Teknik analisis data yang digunakan menggunakan analisis perhitungan value for money dan cost effectiveness analysis. Hasil penelitian menunjukkan bahwa program tidak efektif. Hal tersebut dapat terjadi karena pencapaian output hanya tercapai 90,63% terdapat hambatan pada tahun anggaran 2019 yang berkaitan dengan kesulitan masyarakat dalam melengkapi berkas persyaratan dan minimnya sumber daya manusia. Kemudian, hasil cost effectiveness menunjukkan bahwa program PTSL merupakan program dengan biaya yang murah untuk dijalankan jika dibandingkan dengan penerbitan sertifikat tanah melalui program rutin (pekerjaan rutin) Badan Pertanahan Nasional.